PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PRAKTIK JUAL BELI PAKAIAN BEKAS IMPOR DI PASAR SENEN JAYA - Firda Khoirun Nisya (Universitas Semarang, 2021)
Imported used clothing business is actually contrary to Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection and Regulation of the Minister of Trade of the Republic of Indonesia Number 51 / M-Dag / Per / 7/2015 of 2015 concerning the Prohibition of Importing used imported clothing, it is said that imported used clothes has the potential to be dangerous to human health so it is not guaranteed if it is used and used by the community. In the practice of imported used clothing business, there are still many business actors who do not convey honestly about the condition of the goods being traded. There are even some business actors who cheat and take advantage of consumer weaknesses.The researcher is interested in discussing the form of consumer protection against the practice of buying and selling imported used clothes in Pasar Senen Jaya in terms of Law No.8 of 1999 concerning Consumer Protection and the supervision carried out by the managers of the Senen market on the practice of buying and selling imported used clothes in Senen Jaya Market. The research method used in this research is juridical empirical research methods, researchers run direct observation in Jakarta Senen Market. As well as using primary data and secondary data to help this research. The results obtained Used clothing sales practices in the market Senen jJaya import a number of businesses are pretty much break the rules as set out in the Act - Consumer Protection Act.